Bioturbation as a key driver behind the dominance of Bacteria over Archaea in near-surface sediment - Xihan Chen (Nature Portfolio, 2017)
Abstract The factors controlling the relative abundances of Archaea and Bacteria in marine sediments are poorly understood. We determined depth distributions of archaeal and bacterial 16S rRNA genes by quantitative PCR at eight stations in Aarhus Bay, Denmark. Bacterial outnumber archaeal genes 10–60-fold in uppermost sediments that are irrigated and mixed by macrofauna. This bioturbation is indicated by visual observations of sediment color and faunal tracks, by porewater profiles of dissolved inorganic carbon and sulfate, and by distributions of unsupported 210Pb and 137Cs. Below the depth of bioturbation, the relative abundances of archaeal genes increase, accounting for one third of 16S rRNA genes in the sulfate zone, and half of 16S rRNA genes in the sulfate-methane transition zone and methane zone. Phylogenetic analyses reveal a strong shift in bacterial and archaeal community structure from bioturbated sediments to underlying layers. Stable isotopic analyses on organic matter and porewater geochemical gradients suggest that macrofauna mediate bacterial dominance and affect microbial community structure in bioturbated sediment by introducing fresh organic matter and high-energy electron acceptors from overlying seawater. Below the zone of bioturbation, organic matter content and the presence of sulfate exert key influences on bacterial and archaeal abundances and overall microbial community structure.